Anticoagulation knowledge in patients with atrial fibrillation: An Australian survey - Obamiro, K.; Chalmers, Leanne; Lee, K.; Bereznicki, B.; Bereznicki, L. (Wiley-Blackwell Publishing, 2018)
© 2018 John Wiley & Sons Ltd Background: Atrial fibrillation (AF) is the most commonly diagnosed arrhythmia in clinical practice, and is associated with a significant medical and economic burden. Anticoagulants reduce the risk of stroke and systemic embolism by approximately two-thirds compared with no therapy. Knowledge regarding anticoagulant therapy can influence treatment outcomes in patients with AF. Objective: To measure the level of anticoagulation knowledge in patients with AF taking oral anticoagulants (OACs), investigate the association between patient-related factors and anticoagulation knowledge, and compare these results in patients taking warfarin and direct-acting oral anticoagulant (DOACs). Methods: Participants were recruited for an online survey via Facebook. Survey components included the Anticoagulation Knowledge Tool, the Perception of Anticoagulant Treatment Questionnaires (assessing treatment expectations, convenience and satisfaction), a modified Cancer Information Overload scale and the Morisky Medication Adherence Scale. Treatment groups were compared and predictors of OAC knowledge were identified. Results: Participants taking warfarin had a higher knowledge score compared with those taking DOACs (n = 386, 73% ± 13% vs 66% ± 14%, P < .001). Advancing age, type of OAC, health information overload and ease of OAC use (treatment expectation) were significant predictors of knowledge. Treatment expectation, including the belief that OAC treatment would cause bleeding side effects, varied significantly between participants taking warfarin and DOACs (P =.011). Conclusion: The study identified knowledge gaps in patients taking OACs, and these deficiencies appeared to be greater in participants taking DOACs. Knowledge assessment should be integrated into patient counselling sessions to help identify and resolve knowledge deficits.